Holistic education – a model based on three pillars from cognitive science. An example from science education - Eliza Rybska; Maciej Błaszak (Problemy Wczesnej Edukacji)
In this conceptual article we present a modular model of holistic education. Within this approach, an educational activity (and a child’s learning that derives from it) can be characterized in three dimensions: 1) safety, inclusion and participation; 2) interaction, cognition and representation; and 3) affective action leading to imagination and creativity. A holistic approach nurturing the full cognitive development of a child requires going beyond what a conventional school offers, but still presumes designed but liberating processes. We provide a neurobiological argument for holistic education supported by evidence for the featured three dimensions of holistic education along with illustrative examples.